Transformation in speech-language and hearing professions in South Africa: undergraduate students’ perceptions and experiences explored - Abrahams, Farieda (My University, 2021)
Background: The professions of Speech- Language Therapy and Audiology in South Africa developed under apartheid, and as such, has historically consisted of, and catered to a predominantly white minority population. More than a quarter of a century into democracy, there continues to be a stark incongruence between the demographic profile of the South African population and the Speech- Language and Hearing (SLH) professions, both in terms of race, but also in terms of linguistic and cultural diversity. The hegemony of the SLH professions has implications for curriculum and clinical service provision. Black students entering the professions face a foreign and unwelcoming institutional culture that excludes and devalues indigenous knowledge production and knowledge use. Finally, informal segregation across racial lines is rife within SLH university departments. While lecturers may be aware of the divide, they are not addressing or remediating the situation, thus perpetuating barriers within SLH lecture rooms. Purpose: The main aim of the study was to explore undergraduate students’ perceptions and experiences of transformation within different South African SLH university programmes. Methods: The study utilised a cross-sectional survey design that was exploratory in nature. The study made use of a self-developed 48 question web-based questionnaire. The study was aimed at undergraduate third and fourth year SLH students at various South African universities. A non-probability purposive sampling technique was employed, with 48 participants from 4 South African universities. Data Analysis: Data was analysed both quantitatively and qualitatively. Closed ended questions were analysed using descriptive- as well as inferential statistics, while thematic analysis was utilised to analyse open- ended questions. Results: SLH students have a basic understanding of what decolonisation means within higher education as well as what transformation of the SLH profession entails. They are optimistic about the positive strides made towards achieving transformation. However, results of the study have laid bare the deficits and challenges that remain in transforming SLH training, curricula, and clinical practice. Participants revealed that lack of appropriate resources, power imbalances, and microaggressions pervade the SLH undergraduate experience. SLH students were not confident when working with interpreters, and have appealed for more comprehensive training in indigenous African languages. Racial, cultural, and linguistic differences were important factors determining group interactions. SLH students identified that lecturers were aware of tensions but chose to ignore them. Participants were anxious about their employment prospects due to their race. Conclusions: The study identified the progress made towards achieving transformation of the SLH professions, as well as the challenges that endure. Results of the study have implications for higher education, the HPCSA SLH Board, and professional associations. This study should compel critical reflection and debate by university lecturers and future SLH professionals on the current situation, with a concrete action plan towards transforming the SLH professions to be reflective of, and address the needs of the majority population of South Africa.
A research project submitted in partial fulfilment of the requirements for the degree Master of Arts in Audiology to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021